Dynamics and function of DNA methylation in plants - Zhang, Huiming; Lang, Zhaobo; Zhu, Jian-Kang (Nature reviews. Molecular cell biology, 2018)
DNA methylation is a conserved epigenetic modification that is important for gene regulation and genome stability. Aberrant patterns of DNA methylation can lead to plant developmental abnormalities. A specific DNA methylation state is an outcome of dynamic regulation by de novo methylation, maintenance of methylation and active demethylation, which are catalysed by various enzymes that are targeted by distinct regulatory pathways. In this Review, we discuss DNA methylation in plants, including methylating and demethylating enzymes and regulatory factors, and the coordination of methylation and demethylation activities by a so-called methylstat mechanism; the functions of DNA methylation in regulating transposon silencing, gene expression and chromosome interactions; the roles of DNA methylation in plant development; and the involvement of DNA methylation in plant responses to biotic and abiotic stress conditions.